INTEGRITAS APARAT PENEGAK HUKUM DAN KEPERCAYAAN PUBLIK: ANALISIS SOSIOLOGI HUKUM DI INDONESIA - Adinda Nurrizkia Hijriani; Nandang Sambas (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
Integrity of law enforcement officers plays a crucial role in shaping public trust toward the legal system. From the perspective of sociology of law, law is not merely a set of written norms but also a social practice influenced by the behavior, values, and culture of legal actors. This article aims to analyze the relationship between the integrity of law enforcement officers and public trust in law enforcement in Indonesia. This research employs a normative juridical method combined with a sociological approach, examining legal doctrines, sociological theories of law, and empirical social phenomena related to law enforcement practices. The study finds that low integrity among law enforcement officers significantly undermines public trust, which in turn weakens the legitimacy and effectiveness of law. Therefore, strengthening the integrity of law enforcement officers is a fundamental prerequisite for building a credible and socially legitimate legal system in Indonesia.